Guest Attitude towards Introducing Automation Using Service Robots in Hotels of Delhi - Rakesh Sharma, Dr Mahesh Uniyal, Dr Neha Sharma (International Journal of Advanced Science and Technology, 2020)
better customer experience. Every industry is running after introducing such services which will not only automate the tasks but also enhance the customer experience. Use of robots is one of such technological trend which is prevailing all around the globe. Robots are providing improvement in terms of accuracy, speed and cost effectiveness. As far as hotel industry is concern, the robotics is in its infancy stage in India. There is no doubt that use of robots hotel industry will provide the above said benefits but it will also attract practical issues related to guest attitude towards their use in hotels. This study explores the excitement level of guest in respect of use of robots in general and particularly in hotels too.  This study makes an attempt to correlate the guest excitement along with guest’s demographic profile. This study also concentrates on finding out the guest attitude about potential use of robots in hotels indicating their level of agreement with the same.Keywords: robots, hotel, attitude, excitement, automation.